Influences of the Low Collision Energies and Isotopic Variants on the Stereodynamics for Reactions Li+DF/TF→LiF+D/T (Journal of Atomic and Molecular Sciences, 2018)
Stereodynamics for Li+DF/TF→LiF+D/T reactions are studied using the quasi-classical trajectory method based on a new potential energy surface constructed by Aguado and Paniaga [J. Chem. Phys. 119 (2003) 10088]. The product angular distributions of $P(θ_r)$ and $P(φ_r),$ which reflect the vector correlation, are calculated and discussed. The average rotational alignment factor $〈P_2(cosθ_r)〉$ as function of the collision energy is also presented. Furthermore, four polarization-dependent differential cross sections (PDDCSs), namely, ${\rm PDDCS}_{00},$ ${\rm PDDCS}_{20},$ ${\rm PDDCS}_{21-}$ and ${\rm PDDCS}_{22+}$ are calculated as well. By comparing the stereodynamics results of the title reactions, we find that the isotopic effects are relatively obvious.